Artificial Intelligence and Sustainable Marketing Research (2020–2025): A Bibliometric Analysis of Thematic Evolution and Authenticity Discourse - Nindya Saraswati (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
While research on Artificial Intelligence (AI) in marketing and on sustainable marketing individually has grown, there is limited systematic understanding of how these two domains intersect, particularly in relation to authenticity. A bibliometric approach is therefore needed to map the intellectual structure, key themes, and emerging trends in this evolving research landscape. This study examines how AI technologies are transforming sustainable marketing practices by enabling authentic environmental and social impact communication. A comprehensive bibliometric analysis was conducted using publications from the Scopus database (2020-2025), with a total of 33 articles and 275 keywords examined. Network visualization and temporal analysis were performed using VOSviewer to map the intellectual structure and evolution of AI-enabled sustainable marketing research. This study reveals a rapidly evolving field characterized by increasing sophistication in AI applications and growing integration between technological and sustainability domains. The findings demonstrate a significant shift from traditional green marketing approaches to data-driven, algorithmically enhanced authenticity verification systems. This study establishes the first comprehensive bibliometrics mapping of the AI-sustainable marketing nexus, revealing how technological advancement is addressing authenticity challenges in environmental and social marketing communications. This study is limited by its reliance on Scopus-indexed publications, which may exclude relevant work in other databases or non-English publications.